2017
DOI: 10.1248/bpb.b16-00992
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Efficacy and Adverse Effects of β-Blocking Agents Used Clinically for Chronic Heart Failure

Abstract: Clinical efficacy and adverse effects of the β-blocking agents, carvedilol, bisoprolol, and metoprolol were analyzed theoretically, and then compared quantitatively, for the purpose of determining their proper use for chronic heart failure. Initially, we evaluated occupancy binding to the β 1 and β 2 receptors (Фss β 1 and Фss β 2 ) by these drugs. Thereafter, we examined the relationship between Фss β 1 values and left ventricular ejection fraction (LVEF) increase rate to determine efficacy. The result showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…The majority of our patients (n = 9) in the Lβ group had Bisoprolol as a prior therapy, and, as other studies have already shown, Bisoprolol already occupies > 80% of the receptors very quickly and for a long time [ 32 , 34 ]; therefore, we would assume here that Landiolol (in combination with Bisoprolol) would have a significantly improved effectiveness in lowering the heart rate compared to Landiolol without prior oral β-blocker therapy (similar to the study by de May et al with Celiprolol in healthy subjects) [ 32 ].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The majority of our patients (n = 9) in the Lβ group had Bisoprolol as a prior therapy, and, as other studies have already shown, Bisoprolol already occupies > 80% of the receptors very quickly and for a long time [ 32 , 34 ]; therefore, we would assume here that Landiolol (in combination with Bisoprolol) would have a significantly improved effectiveness in lowering the heart rate compared to Landiolol without prior oral β-blocker therapy (similar to the study by de May et al with Celiprolol in healthy subjects) [ 32 ].…”
Section: Discussionmentioning
confidence: 78%
“…The degree of β1-receptor occupancy also appears to be dose-dependent. For example, the occupancy of β1 receptors increases after Bisoprolol administration from 24% at 0.625 mg to 71.6% at 5 mg [ 34 ]. This effect may be desirable in the context of chronic diseases (e.g., myocardial infarction, heart failure, hypertension) but is not always desirable in the acute setting.…”
Section: Discussionmentioning
confidence: 99%